Pete the Cat's family road trip - Dean, Kim 1969- (Harper, 2020)
Pete the Cat and his family embark on a road trip vacation around the United States, seeing such cities as Niagara Falls, New Orleans, and Savannah
Keywords: Pete / the Cat (Fictitious character) / Juvenile fiction; Cats / Juvenile fiction; Vacations / Juvenile fiction; Automobile travel / Juvenile fiction; Pete / the Cat (Fictitious character) / Fiction; Cats / Fiction; Vacations / Fiction; Humorous stories; JUVENILE FICTION / Humorous stories; Pete / the Cat (Fictitious character); Automobile travel; Cats; Vacations; Pete / the Cat (Fictional character) / Fiction; Automobile travel / Fiction; Readers (Primary); Children's stories; Readers; Readers (Publications); High interest-low vocabulary books; Fiction; Humorous fiction; Juvenile works